Emancipação no cotidiano: iniciativas igualitárias em sociedades de controle - Cedeño, Alejandra Astrid León (2006)
Is it possible for equalitarian initiatives to work in unequal societies? And if it is, how does it happen? This question guided a dialogue between academic and activist voices in the process of doing this work. Through the academic voices, Chapter 1 presents a way of understanding power and emancipation nowadays. Chapter 2 presents the situated knowledge episthemological view (Haraway, 1995), and with this base, the constructive exchange method. As a part of the activist voices, chapter 3 discusses coexistance through two experiences with an equalitarian interest in Catalonia: the Les naus squat and Coop57 Ethical and solidarity financing cooperative. Chapter 4 relates the collective life of two equalitarian experiences in Venezuela - the Santo Domingo Brazil Cooperative and People 94.5 FM Community Radio . After that encounter, the research question is revisited. First, a temporary and situated understanding of power and emancipation is presented: Of power, trying to comprehend some dynamics that initiatives like these must take care of, so they avoid staying trapped in them; and of emancipation, to understand how can they do it and create new forms of life. Chapter 5, consequently, uses chapter 1 to review of the concepts of power, domination and control. Through this, it proposes power-domination-control as a way of capturing collective potencial, aiming to touch everything and everybody in everyday life, and to do this in multiple and complex ways, which could seem as incoherent between them. It tends to operate ungrounded, without having a center and expanding itself to all of society, and that is what justifies the importance of situating it. Chapter 6 proposes emancipation as a process, or a micro-process of squatting (not invading, but occupying what was ours and was taken from us). Squatting spaces of endless possibilities, that can articulate themselves in ways of struggle in a bigger scale, are constructed in resistance processes in an everyday practical way, in molecular revolution experiences (Guattari, 1984). It is proposed to look at everyday life, place, action and time in an active way, and also defends the importance of anarchist practices in constructing emancipation. For a possible conclusion, chapter 7 discuss initiatives as an alternative of the hegemonic words of group and organization ; it then proposes four methods, or key practices which could serve temporarily to answer the question of how equalitarian initiatives work in control societies, by looking at these very different experiences of four initiatives to get an overall understanding